Determining Learning Activities to Promote Scientific Reasoning in Science Learning: A Literature Review - Husfina Lailiyatus Suaidah; Endang Susantini; Eko Hariyono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: The objective of this study is to analyze learning activities in science learning that can promote scientific reasoning skills and provide the best way to teach it. Method: The method used is a literature review analyzing 20 articles indexed by the Scopus database from 2017 – 2022. There are 200 articles about teaching scientific reasoning in the Scopus database, and 20 articles that focused on science learning were selected. The 20 articles then analyzed the domain of scientific reasoning and learning activities to train it. Results: The results showed that science learning interventions in practicing scientific reasoning can be carried out starting from secondary to higher education levels. The learning interventions can be designed in face-to-face learning by integrating social science phenomena/cases, conducting guided investigations assisted by modules, and implementing argument-based learning or online learning using mobile apps/online simulations. There is a tendency that investigative activities are the most widely used intervention to promote scientific reasoning skills in science learning. Novelty: This study can provide an overview of science learning activities that promote scientific reasoning so that teachers can design the most appropriate learning activities to train students' scientific reasoning.